1998
DOI: 10.1073/pnas.95.8.4404
|View full text |Cite
|
Sign up to set email alerts
|

The identification of a 9- cis retinol dehydrogenase in the mouse embryo reveals a pathway for synthesis of 9- cis retinoic acid

Abstract: The ligand-controlled retinoic acid (RA) receptors and retinoid X receptors are important for several physiological processes, including normal embryonic development, but little is known about how their ligands, all-trans and 9-cis RA, are generated. Here we report the identification of a stereo-specific 9-cis retinol dehydrogenase, which is abundantly expressed in embryonic tissues known to be targets in the retinoid signaling pathway. The membranebound enzyme is a member of the short-chain alcohol dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 47 publications
2
64
0
1
Order By: Relevance
“…It was found that the rostral spinal cord and hindbrain highly express retinaldehydrogenase 2, the enzyme involved in the conversion of retinol into atRA, as well as the cellular retinoic acid-binding protein (CRABP) (34,43,44), two key players in retinoid signaling. However, subsequent isomerization to 9-cis RA is poorly understood (45). In addition, CYP26, which is responsible for the breakdown of RA and, hence, deactivation of RAR or RXR, was found to be expressed in the brain of early embryos (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the rostral spinal cord and hindbrain highly express retinaldehydrogenase 2, the enzyme involved in the conversion of retinol into atRA, as well as the cellular retinoic acid-binding protein (CRABP) (34,43,44), two key players in retinoid signaling. However, subsequent isomerization to 9-cis RA is poorly understood (45). In addition, CYP26, which is responsible for the breakdown of RA and, hence, deactivation of RAR or RXR, was found to be expressed in the brain of early embryos (46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 In RPE, where 11-cis-retinoids are relatively abundant, it appears unlikely that this enzyme could play a major role in the production of 9-cis-retinoic acid unless the reaction occurs in a defined intracellular compartment.…”
Section: High-performance Liquid Chromatography Assaymentioning
confidence: 99%
“…Production-The RDH5 gene product has been implicated in the production of 9-cis-retinal before this aldehyde is further oxidized to 9-cis-retinoic acids (12,14). However, disabling mutations in men and mice produce no embryonic developmental abnormalities (16)(17)(18)(19).…”
Section: Involvement Of Rdh11-14 In Retinoid Transformation and All-tmentioning
confidence: 99%
“…An enzyme encoded by the RDH5 gene (10,11), 11-cis-RDH, was proposed to be responsible for both 11-cis-retinal and 9-cis-retinal production due to its relaxed substrate specificity (12)(13)(14)(15). However, the disruption of this gene in a mouse model led to uninterrupted production of 11-cis-retinal (16,17) and a lack of any embryonic abnormalities.…”
mentioning
confidence: 99%